Antimicrobial Susceptibility of Environmental Non-O1/Non-O139 Vibrio cholerae Isolates - Laviad-Shitrit, Sivan; Sharaby, Yehonatan; Izhaki, Ido; Peretz, Avi; Halpern, Malka (Frontiers in Microbiology, 2018)
Vibrio cholerae serogroups O1 and O139 are the causative agents of cholera disease. There are more than 200 serogroups in this species that are termed V. cholerae non-O1/non-O139. Non-O1/non-O139 strains can cause gastroenteritis and cholera like diarrhoea, wound infections, external otitis, and bacteraemia that may lead to mortality. Previous antimicrobial susceptibility studies were conducted mainly on O1/O139 serogroups and on clinical isolates. Our aim was to study and compare the antimicrobial susceptibilities of non-O1/non-O139 environmental strains isolated from chironomids, fish, and waterfowl. Significant differences were found in the antimicrobial susceptibilities between the environmental strains that were isolated from three different reservoir habitats. Significant increase in MICs of ampicillin and chloramphenicol was found in chironomid isolates from 2009 compared to those from 2005. V. cholerae isolates from different waterfowl species displayed the highest MIC values to chloramphenicol and trimethoprim-sulfamethoxazole (SXT), while chironomid isolates demonstrated the highest MIC values towards ampicillin. Isolates from fish and waterfowl showed high MIC values towards doxycycline. No significant differences were found between the MICs of isolates from the different waterfowl species. The percentage of antimicrobial resistance among V. cholerae isolates from waterfowl was the highest compared to the abundance of antimicrobial resistant isolates from chironomids or fish. The antimicrobial resistance genes can be carried on mobile genetic elements, thus, waterfowl may act as reservoirs for these elements and may spread them all over the globe. Data regarding treatment with antimicrobial agents towards V. cholerae non-O1/non-O139 serogroups is lacking and therefore further studies are needed.